Unique and one of the longest appendix operated recently: a case report - Varghese, Varsha Anna; Khenat, Satyajeet Pravin; Patil, Gaurav Bapu; Jagtap, Mayuresh Chandrakant; Patil, Pushpak Kiran; Kulkarni, Ananta (International Surgery Journal, 2025)
Appendectomy is usually performed as an emergency operation to treat appendicitis, which is when the appendix becomes inflamed and infected due to an obstruction. We present the case of an 18-year-old boy with persistent pain in right iliac fossa, which was clinically diagnosed as appendicitis. On investigations, an ultrasound of abdomen and pelvis revealed inflamed appendix with free fluid surrounding appendix. Exploratory open appendectomy was done. Intraoperatively, it demonstrated a very long 17.2 cm inflamed appendix which was removed successfully and rest was uneventful Postoperatively, patient is doing well on follow-up. Hence, it is concluded that in patients with appendicitis, appendectomy is the definitive management along with antibiotics. If delayed can present as perforated appendix and leading to further complications.